ANALISIS KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA KELAS X SMA PADA MATERI KINEMATIKA GERAK LURUS DI SMA NEGERI PLUS PROVINSI RIAU - Ningsih, Rany Surya; Azhar, Azhar; Syafi’i, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe the level of ability to solve physics problems of 10 th Grade Student in SMA Neger Plus Riau Province. This study is a survey research. The Subject of Research is one class, twenty five student of 10th Grade SMA Negeri Plus Riau in 2017/2018 School Year. Collection of research data obtained by students’ result test to solve physics problem on linear motion kinematics material. This test uses essay questions, those question is given after learned the linear kinematics material. Analysis of this research data is descriptive analysis. Data analysis result show that the average percentage of students' physics problem solving abilities each year is 62.75% for useful description stage (medium category), 21% for physics approach stage (very low category), 57,5% for specific application of physics stage (low category), 56.75% for mathematical procedure stage (low category) and 56.75% for logical progression stage (low category).Key words : Analysis of learning, problem-solving skills, rectilinear motion kinematics material